Cyber-governance of the natural world the implications of digital twins in environmental governance - Paulan Korenhof; Brett Metcalfe; Adam Henschke (Earth System Governance)
Digital Twins (DTs) are data-driven real-time and multi-faceted representations of real-life physical systems or phenomena. Currently, DTs are developed for use in environmental governance, ranging from DTs of single crops to the planet Earth. By offering up-to-date dynamic simulations, DTs are anticipated to support decision-making in addressing key challenges like ecological degradation and climate change. However, DTs are not neutral tools: they are shaped by human assumptions and values, and bring about changes and power shifts in decision-making processes.In this article, we take in a bird's eye view to identify the different levels and manners in which DTs can reconfigure environmental governance. Building on Korenhof et al. (2021), we conceptualise DTs as cybernetic systems. We trace how these systems affect governance on the levels of information, communication, and control. We conclude that, when used in environmental governance, it is vital to take action to ensure the democratic legitimacy of DTs.